Creative Tourism and Mobile Apps: A Comparative Study of Usability, Functionality and Creativity of Travel Apps - Dias, Á.; Melo, J.; Patuleia, M. (International Journal of Hospitality and Tourism Systems, 2022)
The focus of this paper was to create a quantitative study that would compare Usability, Functionalities and Creativity of a few travel apps in the field of Creative Tourism, in order to understand how they affect Use Intention of travel apps. Thus, a questionnaire was applied to tourists who are travel app users. Among 50 respondents visiting Lisbon, 3 apps were classified, TripAdvisor, Air bnb Experiences and Expedia. The findings reveal that tourists perceive that the touristic experiences they are involved in are creative, however it was not possible to ensure a correlation between Creativity of touristic experiences and App Use Intention. Furthermore, results demonstrate a significant correlation between Usability-Use Intention, and App Functionalities-Use Intention.